Framing Analysis: A Comparison of IDN Times and Detik’s Coverage on the Issue of Sexism on Political Campaign Billboard for the Sleman 2024 Regional Elections - Mubaroq, Abdul Khalim (Jogjakarta Communication Conference (JCC), 2025)
The campaign billboard of Sleman 2024 Regent and Deputy Regent candidate number 2 Harda-Danang has drawn controversy because it is considered to contain elements of sexism and contradict the principles of democracy. The billboard reads “Choosing a female imam (leader). Imam (leader) must be male” received attention from the media. This study chose Detik and IDN Times as objects because Detik is ranked first in the news media category, while IDN Times focuses on Generation Z and Millennials who dominate the 2024 election voters. The purpose of the research is to find out the news framing of the two media using the Robert M. Entman model. This study analyzed 6 news stories, 3 from IDN Times and 3 from Detik. The results show that IDN Times emphasizes the issue of gender equality, while Detik sees this event as an objective sequence of events.